Semelparous Death as one Element of Iteroparous Aging Gone Large - Kern, Carina C.; Gems, David (Frontiers in Genetics, 2022)
The aging process in semelparous and iteroparous species is different, but how different? Death in semelparous organisms (e.g. Pacific salmon) results from suicidal reproductive effort (reproductive death). Aging (senescence) in iteroparous organisms such as humans is often viewed as a quite different process. Recent findings suggest that the nematode Caenorhabditis elegans, widely used to study aging, undergoes reproductive death. In post-reproductive C. elegans hermaphrodites, intestinal biomass is repurposed to produce yolk which when vented serves as a milk to support larval growth. This apparent benefit of lactation comes at the cost of intestinal atrophy in the mother. Germline removal and inhibition of insulin/IGF-1 signaling (IIS) suppress C. elegans reproductive pathology and greatly increase lifespan. Blocking sexual maturity, e.g. by gonadectomy, suppresses reproductive death thereby strongly increasing lifespan in semelparous organisms, but typically has little effect on lifespan in iteroparous ones. Similarly, reduced IIS causes relatively modest increases in lifespan in iteroparous organisms. We argue that the more regulated and plastic mechanisms of senescence in semelparous organisms, involving costly resource reallocation under endocrine control, exist as one extreme of an etiological continuum with mechanisms operative in iteroparous organisms. We suggest that reproductive death evolved by exaggeration of mechanisms operative in iteroparous species, where other mechanisms also promote senescence. Thus, knowledge of C. elegans senescence can guide understanding of mechanisms contributing to human aging.